Mechanism of Ba Zhen Tang Delaying Skin Photoaging Based on Network Pharmacology and Molecular Docking - Han M; Li H; Ke D; Tian LM; Hong Y; Zhang C; Tian DZ; Chen L; Zhan LR; Zong SQ (Dove Medical Press, 2022)
Miao Han,1,* Heng Li,2,* Dan Ke,3 Li-Ming Tian,4 Yi Hong,5 Chong Zhang,6 Dai-Zhi Tian,6 Long Chen,4 Li-Rui Zhan,4 Shi-Qin Zong4 1Department of Dermatology, School of Medicine, Jianghan University, Wuhan, People's Republic of China; 2Department of Dermatology, Hubei Provincial Hospital of Traditional Chinese Medicine, Hospital Affiliated to Hubei University of Chinese Medicine, Wuhan, People's Republic of China; 3Department of Dermatology, Chongqing Traditional Chinese Medicine Hospital, Chongqing, People's Republic of China; 4Department of Dermatology, Wuhan No.1 Hospital, Hospital of Traditional Chinese and Western Medicine Affiliated to Hubei University of Chinese Medicine, Wuhan Hospital of Traditional Chinese and Western Medicine Affiliated to Tongji Medicine College of Huazhong University of Science and Technology, Wuhan, People's Republic of China; 5College of Pharmacy, Hubei University of Chinese Medicine, Wuhan, People's Republic of China; 6Institute of Geriatrics, Hubei University of Chinese Medicine, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Li-Ming Tian, Department of Dermatology, Wuhan No.1 Hospital, Hospital of Traditional Chinese and Western Medicine Affiliated to Hubei University of Chinese Medicine, Wuhan Hospital of Traditional Chinese and Western Medicine Affiliated to Tongji Medicine College of Huazhong University of Science and Technology, No. 215 of Zhongshan Avenue, Qiaokou District, Wuhan, 430022, People's Republic of China, Tel +86 27 8533 2606, Fax +86 27 8583 2563, Email jolly0731@126.comPurpose: To study the efficacy of Ba Zhen Tang in delaying skin photoaging and its potential mechanism based on network pharmacology and molecular docking.Methods: First, we screened the active components and targets of Ba Zhen Tang by Traditional Chinese Medicine Database and Analysis Platform (TCMSP) and The Universal Protein Resource (UniProt). The target genes of skin photoaging were obtained from GeneCards and GeneMap database. Then, we analyzed the protein-protein interaction (PPI) by STRING database. The network map was constructed by Cytoscape. Finally, we performed Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis by Metascape database. The molecular docking via Autodock Vina and Pymol. Furthermore, skin photoaging cellular models were established, and the effects of Ba Zhen Tang on ameliorating skin photoaging were investigated.Results: A total of 160 active ingredients in Ba Zhen Tang and 60 targets of Ba Zhen Tang for delaying skin photoaging were identified. By GO enrichment analysis, 1153 biological process entries, 45 cellular component entries and 89 molecular functional entries were obtained. A total of 155 signal pathways were obtained by KEGG analysis. Ba Zhen Tang is related to MAPK signaling pathway, TNF signaling pathway and AGE-RAGE signaling pathway in diabetic complications, etc., which directly affect the key nodes of photoaging. The molecular docking results showed that there was a certain affinity between the main compounds (kaempferol, quercetin, β-sitosterol, naringenin) and core target genes (PTGS2, CASP3, MAPK1, MAPK3, TP53). Ba Zhen Tang-treated mouse serum inhibited the senescence and p16INK4a expression of human immortalized keratinocyte (HaCaT) cells irradiated by ultraviolet-B (UVB).Conclusion: Our study elucidated the potential pharmacological mechanism of Ba Zhen Tang in the treatment of photoaging through multiple targets and pathways. The therapeutic effects of Ba Zhen Tang on skin photoaging were validated in cellular models.Keywords: Ba Zhen Tang, skin photoaging, network pharmacology, molecular docking, mechanism